Detecting Lecturer Dominance and Thai Student Participation in BIPA Learning: Deep Learning-Based Discourse Analysis - Eva Ardiana Indrariani; Aziizatul Khusniyah; Waewalee Waewchimplee (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
The purpose of this study is to examine Indonesian for Foreign Speakers (BIPA) instruction from a deep learning standpoint, with an emphasis on determining lecturer dominance patterns and Thai students' levels of cognitive participation. With an inherent case study design, a qualitative technique is employed. A discourse analysis framework developed by Sinclair and Coulthard (1975) and deep learning indicators developed by Marton and Säljö (1976) and Biggs and Tang (2011) were used to record, transcribe, and analyze utterances from learning encounters at an Islamic university in Indonesia. The study's conclusions show that the conventional Initiation-Response-Feedback (IRF) structure dominates the communication pattern, which underlies the low student participation (86.5%) and the predominance of lecturer speech (70.1%). Variations in patterns, however, including IRF(IR), IIRF, and particularly I→R→I, have been demonstrated to foster a dialogue space that promotes higher-level cognitive engagement, including cultural comparison and critical reflection. The flexibility of communication patterns that permit meaning negotiation and student elaboration, rather than a single pattern, determines the quality of deep learning in BIPA, according to the study's findings. In practice, this means that BIPA teachers must intentionally create communication tactics that encourage student initiative and introspection in order to make the BIPA classroom a meaningful and dialogic micro-diplomatic environment.   Penelitian ini bertujuan untuk mengidentifikasi pola dominasi pengajar dan tingkat partisipasi kognitif students Thailand dalam pembelajaran BIPA (Bahasa Indonesia bagi Penutur Asing) dari perspektif pembelajaran mendalam (deep learning). Dengan desain studi kasus kualitatif, kerangka analisis wacana Sinclair dan Coulthard (1975) serta indikator deep learning dari Marton dan Säljö (1976) dan Biggs dan Tang (2011) digunakan untuk merekam, mentranskripsi, dan menganalisis tuturan pembelajaran BIPA di sebuah universitas Islam di Indonesia. Hasil penelitian menunjukkan bahwa pola Inisiasi-Respon-Umpan Balik (IRF) konvensional mendominasi komunikasi (70,1% tuturan pengajar BIPA). Partisipasi students Thailand didominasi respons minimal dan translatif (86,5%), sementara partisipasi elaboratif yang mencerminkan keterlibatan kognitif tingkat tinggi hanya 13,5%. Namun, variasi pola seperti IRF(IR), IIRF, dan terutama I→R→I terbukti membuka ruang dialog yang mendorong perbandingan budaya, refleksi kritis, dan negosiasi makna. Fleksibilitas pola komunikasi, bukan pola tunggal, menentukan kualitas deep learning di BIPA. Secara praktis, pengajar BIPA perlu merancang strategi komunikasi yang memicu inisiatif dan elaborasi students agar kelas BIPA menjadi lingkungan mikro-diplomatik yang dialogis dan bermakna.